Yves Bonnefoy: the performative and the negative - McLaughlin, E (2012)
This thesis examines Bonnefoy’s cultivation of the performative aspects of the poetic act in his later collections of poetry. It investigates the poet’s use of the theatrical structures of poetic performance, their temporal and spatial dynamics, to deconstruct conceptual or representative modes of thought. It examines how Bonnefoy uses apostrophes to insentient phenomena and addresses to an unidentified other in his attempts to open language up to the finitude and sharing of existence. Working within language, against language, the poet cultivates what he describes as ‘un savoir, tout négatif et instable qu’il soit, que je puis peut-être nommer la vérité de la parole’. The first chapter of this thesis investigates how the image of the ephemeral flame becomes a model for a finite poetic performance in ‘La Terre’. The second chapter scrutinises how Bonnefoy makes the signifying function of language ‘passive’ to the inappropriable excess of material presence in Début et fin de la neige. The third chapter, analysing ‘La Voix lointaine’, explores how Bonnefoy dramatises the experience of self-presence as the act of listening to a distant voice. The fourth chapter, investigating the relationship between finitude and form in ‘L’Heure présente’, analyses how the dissolution of form gives rise to a form that is always à venir, a dynamic, ‘un possible’.